Sanksi terhadap Penyalahgunaan Pemakaian Listrik di Wilayah Perusahaan Listrik Negara (Persero) Rayon Kuta - I Made Ariana; Ida Ayu Putu Widiati; A.A Sagung Laksmi Dewi (Warmadewa Press, 2020)
The relationship between PT. PLN (Persero) and the electricity user is a selling and purchasing whose provisions are set forth in an agreement called Surat Perjanjian Jual Beli Tenaga Listrik (SPJBTL). Based on the occurring phenomenon, the problem of abuse of electricity usage, especially that occurred in the last three years in the service area of PLN Rayon Kuta, is extremely detrimental to the state in this case the PLN. This study reveals the factors that lead to misuse of electricity usage and the application of sanctions against misuse of electricity in the PT. PLN (Persero) Rayon Kuta with empirical legal research. The abuse of the electricity in Kuta and its surrounding areas are motivated by several factors including ignorance, intention, external customer and customer negligence. From some of the physical evidence found by T2 P2TL PT. PLN (Persero) Kuta rayon, several forms of abuse of electricity consumption can be categorized, among others such as affect power barriers, measurement, and wild connection outside the measurement. In the case of the settlement of the abuse of the electricity usage, PLN uses the legal basis of the regulation of directors of PT. PLN (Persero) Number: 088-Z.P / DIR / 2016 concerning the Controlling of Electricity Usage. To minimize the occurrence of abuse of electricity usage, it is necessary to optimize socialization related to the right and safe electricity usage by PLN in cooperation with other related parties such as university level education, environment or village apparatus and especially in Bali the PT. PLN should cooperate with the management or kelian (the leader of a customary group of community called banjar) under certain mechanism. The application of sanctions to PLN customers or users who are found to be abusing the use of electricity need to consider the legal benefit, especially those found to violate Category IV in order to make the process of settlement through the legal sphere to create a deterrent effect so that in the future similar incidents affecting the state losses and other public losses as electricity users can be reduced or minimized.